Sporadic Human Cryptosporidiosis Caused by Cryptosporidium cuniculus, United Kingdom, 2007–2008 - Chalmers, Rachel M. (Centers for Disease Control and Prevention, 2011)
To investigate sporadic human cryptosporidiosis trends in the United Kingdom, we tested 3,030 Cryptosporidium spp.–positive fecal samples, submitted for routine typing in 2007–2008, for C. cuniculus. C. cuniculus prevalence was 1.2%; cases were mostly indigenous and occurred across all age groups. Most occurred during August–October and may be linked to exposure opportunities.